2022
DOI: 10.1186/s13007-022-00885-z
|View full text |Cite
|
Sign up to set email alerts
|

Organellar microcapture to extract nuclear and plastid DNA from recalcitrant wood specimens and trace evidence

Abstract: Background Illegal logging is a global crisis with significant environmental, economic, and social consequences. Efforts to combat it call for forensic methods to determine species identity, provenance, and individual identification of wood specimens throughout the forest products supply chain. DNA-based methodologies are the only tools with the potential to answer all three questions and the only ones that can be calibrated “non-destructively” by using leaves or other plant tissue and take adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Based on microscopic observations of ray parenchyma cells in C. bungei ‘Jinsi’ SW, the nucleus was spherical in shape. Spherical nuclei were also observed in Bridelia retusa [ 48 ] and Carya ovata [ 49 ]. It has been reported that the nuclear shape of SW ray cells in Populus sieboldii × P. grandidentata trees was fusiform or spindle [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on microscopic observations of ray parenchyma cells in C. bungei ‘Jinsi’ SW, the nucleus was spherical in shape. Spherical nuclei were also observed in Bridelia retusa [ 48 ] and Carya ovata [ 49 ]. It has been reported that the nuclear shape of SW ray cells in Populus sieboldii × P. grandidentata trees was fusiform or spindle [ 50 ].…”
Section: Discussionmentioning
confidence: 99%